EUPHEMISM, POLITICAL CORRECTNESS AND LANGUAGE CHANGE - Rabiyeva M.G. (International Journal of Literature and Language Studies, 2026)
This article is devoted to a linguistic denomination so called politically correct language, which had a considerable influence on modern English and was broadly adopted in English-speaking countries. In addition, this article discusses the present problem of the use of politically correct language within the bounds of intercultural communication. Studying the use of politically correct language facilitates intercultural communication and helps to understand better the role of a language in society, the interrelation between a language and culture. Besides, the article deals with a 'people first' approach and its impact on language change